PELAKSANAAN TUGAS STEWARD DALAM MENJAGA KEBERSIHAN PERALATAN DI KITCHEN SECTION GRAND JATRA HOTEL PEKANBARU - Rianda, Anggita Vellya; ', Etika (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Grand Jatra Hotel is a 5-star hotel that stands right in the city center of the Pekanbaru Riau region. Hotels can be judged successful or not from the facilities and services provided to their guests. In addition to guest satisfaction, guest health is also very important to note. All departments in the hotel provide the best service for guests who come to fulfill guest satisfaction and health while staying at the hotel. Including the cleanliness of the kitchen work environment, the equipment used, the maintenance of food ingredients, and the processing operations that run. In every hotel must have their own obstacles in each department. Including the kitchen section. One of the obstacles is the cleanliness of the equipment in the kitchen. Stewards are an important part of maintaining cleanliness in the kitchen, so that the products, environment, and tools in the kitchen are always kept clean and free from germs or bacteria that can contaminate food and drinks that will be served to guests. This study was conducted to analyze the obstacles that occur to stewards in maintaining the cleanliness of equipment in the kitchen. This study uses qualitative method research. Data collection was carried out by conducting observations and continued with interviews and documentation. Keywords : Hotel, Steward, Equipment